2021
DOI: 10.1111/trf.16612
|View full text |Cite
|
Sign up to set email alerts
|

Plasmavigilance—Adverse events among US Source plasma donors

Abstract: Background: Source plasma (SP) is the primary starting material for 87% of plasma-derived medicinal products globally. Plasmavigilance is a program designed to collect, analyze, and monitor donor adverse events (AEs) across the SP collection industry. Donor retention depends on donors having a safe and satisfactory experience. This study analyzes AE rates and SP donor characteristics that may be predictors of an AE. Study Design and Methods: Donation data for 1.1 million donors making 12,183,182 SP donations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…Thus, the rate of DAEs in our study was slighter lower than those reported by Schreiber et al; however, not all DAEs result in deferral and we are only reporting cases where donors were deferred due to an adverse event. Similar to our study, the most common DAEs observed were hypotensive (8.32 per 10 000) and phlebotomy (5.91 per 10 000) related 23 . Together, these two categories comprised ~90% of all DAEs.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, the rate of DAEs in our study was slighter lower than those reported by Schreiber et al; however, not all DAEs result in deferral and we are only reporting cases where donors were deferred due to an adverse event. Similar to our study, the most common DAEs observed were hypotensive (8.32 per 10 000) and phlebotomy (5.91 per 10 000) related 23 . Together, these two categories comprised ~90% of all DAEs.…”
Section: Discussionsupporting
confidence: 87%
“…Schreiber et al recently analyzed 1.1 million SP donors that made 12 183 182 donations over a 4‐month period. 23 They found that the DAE rate was 15.85 per 10 000 donations. 23 In our study, the rate of DAEs was 6.97 per 10 000 donations in 2017‐2018, 14.84 per 10 000 donations in 2018‐2019, and 13.38 per 10 000 donations in 2019‐2020.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations